2019
DOI: 10.5514/rmac.v45.i2.75582
|View full text |Cite
|
Sign up to set email alerts
|

Transitions From Rich-to-Lean Schedules Increase Attack in a Laboratory Model of Social Aggression in Pigeons: Ii. Fixed-Interval Schedules.

Abstract: Pigeons key pecked under two-component multiple fixed-interval (FI) schedules. Each component provided a different reinforcer magnitude (small or large), signaled by the color of the key light. Attacks toward a live, protected target pigeon were measured. Large- (rich) and small- (lean) reinforcer components alternated irregularly such that four different interval types (transitions) between the size of the immediately preceding reinforcer and the size of the upcoming reinforcer occurred within each session: l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Because we cannot force the pigeon to start work on the FR schedule, we must seek other ways to measure the disruptive effects of richlean transitions. An interesting possibility is suggested by the research showing that pigeons will engage in social aggression (Pitts et al, 2019;Williams et al, 2019) and rats will consume ethanol (Sawyer et al, 2019) during the rich-lean transition. Will advance notice of a lean component affect the likelihood, duration, or intensity of the aggression or ethanol consumption?…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because we cannot force the pigeon to start work on the FR schedule, we must seek other ways to measure the disruptive effects of richlean transitions. An interesting possibility is suggested by the research showing that pigeons will engage in social aggression (Pitts et al, 2019;Williams et al, 2019) and rats will consume ethanol (Sawyer et al, 2019) during the rich-lean transition. Will advance notice of a lean component affect the likelihood, duration, or intensity of the aggression or ethanol consumption?…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it is worth noting that pigeons will respond to turn off a stimulus correlated specifically with the richlean transition (Perone, 2003;Retzlaff et al, 2017). When afforded an opportunity to do so, pigeons will also attack another pigeon during the rich-lean transition (Pitts et al, 2019;Williams et al, 2019)-behavior not unlike some of the problematic transitionrelated behavior observed in clinical settings. The generality of the disruptive effect of richlean transitions makes a prima facie case for using Perone and Courtney's procedure as a model of transition-related problem behavior as it occurs in homes, schools, and clinical settings.…”
mentioning
confidence: 99%
“…Despite some of the issues/limitations discussed above, the present data add to converging evidence indicating that signaled rich‐to‐lean transitions function aversively. This evidence includes data showing that a) escape is more probable during rich‐to‐lean than during the other transition types (Everly et al, 2014; Retzlaff et al, 2017), b) subjects choose mixed‐schedule over multiple‐schedule stimuli during rich‐to‐lean transitions (Langford et al, 2019), c) schedule‐induced aggression is more prevalent during rich‐to‐lean transitions than during the other transition types (Pitts et al, 2019; Williams et al, 2019), d) problem behavior in individuals with developmental disabilities can be induced by transitions from more preferred or higher‐density reinforcement conditions to less preferred or lower‐density reinforcement conditions (Castillo et al, 2018; Jessel et al, 2016), and e) rich‐to‐lean transitions can be used as a form of error correction (Jessel, et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Falk, 1971) during rich‐to‐lean arrangements. In such studies, rich‐to‐lean transitions increased rates of adjunctive attack (Pitts et al, 2019; Williams et al, 2019) and fluid consumption (water and sucrose solution, Galuska & Sawyer, 2017; ethanol, Sawyer et al, 2019) relative to other transition types.…”
mentioning
confidence: 99%
“…The subject is exposed to any of several schedules (e.g., extinction, fixed-and variable-ratio, fixed-and variable-interval, fixed-and random-time, differential-reinforcement-of-low-rate schedules) and simultaneously allowed the opportunity of attacking a target. The target has been either a live restrained conspecific (Azrin, et al, 1966;Gentry, 1968;Knutson, 1970;Pitts, Hughes, & Williams, 2019, this issue for pigeons; Hutchinson & Renfrew, 1978;Knutson & Schrader, 1975;Thompson & Bloom, 1966 for rats), an inanimate target such as a taxidermically stuffed bird (Azrin et al, 1966;Flory, 1969aFlory, , 1969b, a mirror image (Cohen & Looney, 1973), a slide image (Flory & Ellis, 1973), or a picture of a conspecific (Looney & Cohen, 1974;Looney, Cohen, & Yoburn, 1976). When given intermittent access to a reinforcer or extinction, many species including humans (e.g., Frederiksen & Peterson, 1974;Harrell, 1972;Hutchinson, Pierce, Emley, Proni, & Sauer, 1977;Kelly & Hake, 1970) engage in aggressive behavior toward a target.…”
Section: Introductionmentioning
confidence: 99%